POTENSI ZAKAT PERBANKAN SYARIAH DI INDONESIA - Indah Indah; Zainuddin Zainuddin (Tamwil, 2021)
This research aims to analyze the potential of corporate zakat of Indonesian Islamic banks. This is qualitative research. Financial reports of 13 Islamic Banks in Indonesia, published and made available online through their website for 2017-2018, were analyzed using content analysis techniques. The research findings show that overall, corporate zakat paid by Islamic banks in Indonesia is still 6% of total zakat potential, calculation of corporate zakat using “net asset” method results in the most outstanding value of zakat potential-approximately 711 billion Rupiah or ten times of the amount of zakat that Islamic banks have paid in Indonesia.